An Evaluation of the Online Course on Climate Change and Emotion (International Conference on Computers in Education, 2022)
Education possesses the potential to enable people to understand the causes and consequences of climate change, make informed decisions and take appropriate actions to address it. Behavioral research shows that decision-making is a cognitive-emotional process. Therefore, any intervention to enable appropriate actions for climate change must include the knowledge and skills necessary to enable sustainable living. Based on such an integrated model, an online interactive course was designed for middle school learners in the age group of 12-15 years. Here, we present the design of the course and a pilot study conducted (N=52) to investigate the efficacy of the course. Efficacy was assessed through a self-reported pre-post Sustainable Development Self-Efficacy (SDSE) questionnaire. A paired sample t-test between the post-and pre-test SDSE questionnaire scores revealed a significantly increased score (p < 0.05). Specifically, increased scores were seen on the subscales of “Influence of environment” (p < 0.05) and “Economic welfare” (p < 0.05). This study provides preliminary evidence of an online course to build knowledge of climate change and mindsets to affect pro-environmental action to mitigate its impact.